Donkey Work : Congressional Democrats in Conservative America, 1974-1994 - Andelic, Patrick Kieron, 1987- (Book collections on Project MUSE., 2019)
"What happened to the Democratic Party after the 1960s? Most political histories assume that the latter third of the twentieth century belongs to the American conservative movement. But narratives of conservative triumph and liberal disintegration cannot account for the policy failures that conservatives encountered, especially their inability to significantly reduce the scope of the federal government. By re-examining the fortunes of the Democratic Party after 1974, Patrick Andelic challenges the idea of a liberal retreat on all fronts after the 1960s. Andelic argues that "presidential synthesis" (the interpreting of American political history through the prism of presidential administrations) often has the effect of obscuring longer trends. He focuses instead on Congress during this period, which has remained chronically understudied by historians. It was in Congress that Democratic strength proved the most durable. Throughout the 1970s and 1980s, the Democrats maintained control of the House of Representatives and, for all but six years, the Senate as well. By the late 1980s, some commentators began to speak of a "permanent Democratic majority" in Congress. By pulling the focus away from the White House to Capitol Hill, Andelic reveals the overlooked robustness of the Democrats after 1972"--